Strategy to Strengthen State Administrative Law in Eradicating Corruption Practices by State Administration Officials: Strategi Penguatan Hukum Administrasi Negara Dalam Memberantas Praktik Korupsi Yang Dilakukan Pejabat Administrasi Negara - Charren Hendrik (Universitas Negeri Semarang, 2022)
The lenient regulation of State Administrative Law is giving the practice of corruption an opportunity to take place in the enforcement of Indonesian governance. When in reality, the State Administrative Law is supposed to regulate various state administration activities, in which taking care of the practice of corruption being one of them. Therefore, this research offers strategies of the eradication of corrupt practices that have inflicted the state’s financial loss. The eradication can be done by reinforcing the implementation of a proper government. Various attempts are required to be done in order to construct a corruption-free governance’s structure, such as, applying the principle of good governance and closed bureaucratic system in the practice of the state’s enforcement; establishing a leadership spirit in a righteous governance to escalate the integrity and ethics of the state’s enforcement in order to steer clear from deviation and abuse of power; reinforcing the State Administrative Law by establishing strict, definite, and measurable laws; conducting and reinforcing anti-corruption establishment in both the state’s central and the countryside. The method of research applied is normative law research, which is by studying the law’s regulation in the Constitution and describing the role of the State Administrative Law as the authorized regulation that has the power to combat the crime of corruption.